2011
DOI: 10.1242/jeb.051607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body mass on physiological and anatomical parameters of mature salmon: evidence against a universal heart rate scaling exponent

Abstract: Clark et al., 2010) and took advantage of the diverse life history of Chinook salmon (Oncorhynchus tshawytscha), the largest of the Pacific salmonids (Groot and Margolis, 1991). After emerging from the egg with a M b of <1g (Kinnison et al., 1998), juvenile Chinook salmon typically remain in freshwater for around 1year prior to commencing an ocean migration to grow and mature. Whereas the majority of individuals spend around 3years in the ocean and return to freshwater spawning grounds as 4year olds, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…While it was not possible to measure heart rate recovery in jacks in the present study, this is an obvious next step once appropriately-sized technology is developed. Nevertheless, resting heart rate is not dependent on body mass in mature Chinook salmon spanning a mass range of 2.7 to 16.8 kg [33], and cardiac output scales isometrically in Chinook salmon over the body mass range that has been examined to date (2.1–5.4 kg; [5], [33]). Others have demonstrated for a range of fish species that gill surface area generally scales with body mass with an exponent around 0.8 [34], [35], which is expectedly lower than the scaling exponent of 1.06 determined for the gill basket mass of coho salmon in the present study (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While it was not possible to measure heart rate recovery in jacks in the present study, this is an obvious next step once appropriately-sized technology is developed. Nevertheless, resting heart rate is not dependent on body mass in mature Chinook salmon spanning a mass range of 2.7 to 16.8 kg [33], and cardiac output scales isometrically in Chinook salmon over the body mass range that has been examined to date (2.1–5.4 kg; [5], [33]). Others have demonstrated for a range of fish species that gill surface area generally scales with body mass with an exponent around 0.8 [34], [35], which is expectedly lower than the scaling exponent of 1.06 determined for the gill basket mass of coho salmon in the present study (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Since ventricle mass scales isometrically with body mass in salmonids (Fig. 3C; [33]), it may be reasonable to assume that cardiac stroke volume also scales proportionally. While it was not possible to measure heart rate recovery in jacks in the present study, this is an obvious next step once appropriately-sized technology is developed.…”
Section: Discussionmentioning
confidence: 99%
“…heartbeat and breathing rate: see Millidine, Metcalfe & Armstrong, 2008;Green, 2011;Bishop & Spivey, 2013; but note that even variation in heartbeat may not always be congruent with that of metabolic rate developmentally, allometrically or in response to temperature change: Barrionuevo & Burggren, 1999;Clark & Farrell, 2011;. heartbeat and breathing rate: see Millidine, Metcalfe & Armstrong, 2008;Green, 2011;Bishop & Spivey, 2013; but note that even variation in heartbeat may not always be congruent with that of metabolic rate developmentally, allometrically or in response to temperature change: Barrionuevo & Burggren, 1999;Clark & Farrell, 2011;.…”
Section: (8) Temperature Effectsmentioning
confidence: 99%
“…However, b m values far from 1.0 have also been observed in some species [4], [7], [32]. It has been suggested that further experimental analysis is required to study the intraspecific scaling exponents in species that span a wide range of M [33][34].…”
Section: Introductionmentioning
confidence: 99%